Association between the diagnosis-to-treatment interval and overall survival in Taiwanese patients with oral cavity squamous cell carcinoma. (February 2017) - Liao, Chun-Ta; Chen, Hsin-Ni; Wen, Yu-Wen; Lee, Shu Ru; Ng, Shu-Hang; Liu, Tsang-Wu; Tsai, Sen-Tien; Tsai, Ming-Hsui; Lin, Jin-Ching; Lou, Pei-Jen; Wang, Cheng Ping; Chu, Pen-Yuan; et al.
Abstract: Background: To investigate the association between the diagnosis-to-treatment interval (DTI) and overall survival (OS) in patients with oral cavity squamous cell carcinoma (OSCC). Methods: A total of 18, 677 patients with first primary OSCC identified in the Taiwanese Cancer Registry Database between 2004 and 2010 were examined. The effect of DTI on 5-year OS rates was investigated with multivariate Cox regression analysis. After the identification of the optimal cutoff for DTI based on the 5-year OS rates, DTI was classified in the following 20-day groups: ≤20 days (57% of the study patients), 21–45 days (34%), 46–90 days (6%) and ≥91 days (3%). In additional exploratory analyses, DTI was reclassified in the following 30-day interval groups: ≤30 days (81% of the study patients), 31–60 days (14%), 61–90 days (2%) and ≥91 days (3%). Results: Multivariate analyses identified DTI (≤20 days versus other subgroups), sex (female versus male), age (<65 versus ≥65 years), clinical stage (p-stage I versus p-stage II, III, IV) and treatment modality (initial surgery versus initial non-surgery) as independent prognostic factors for 5-year OS. Compared with a DTI ≤20 days, the DTI categories ≥91 days (hazard ratio [HR]: 1.28, P  < 0.001), 46–90 days (HR: 1.25, P  < 0.001) and 21–45 days (HR: 1.07, P  = 0.007) were independently associated with a higher risk of 5-year mortality. Similar results were obtained for DTI ≤30 days groups. Conclusions: DTI is independently associated with 5-year OS in OSCC patients. A DTI longer than 30 days or even 20 days may potentially decrease survival. Highlights: It is still unclear whether delayed treatment can negatively affect survival in oral cavity squamous cell carcinoma. A prolonged diagnosis-to-treatment interval (DTI) was an adverse prognostic factor. A DTI longer than 20–30 days may potentially decrease overall survival.